2021
DOI: 10.1093/braincomms/fcab269
|View full text |Cite
|
Sign up to set email alerts
|

Brain atrophy progression in Parkinson’s disease is shaped by connectivity and local vulnerability

Abstract: Brain atrophy has been reported in the early stages of Parkinson’s disease, but there have been few longitudinal studies. How intrinsic properties of the brain, such as anatomical connectivity, local cell-type distribution and gene expression combine to determine the pattern of disease progression also remains unknown. One hypothesis proposes that the disease stems from prion-like propagation of misfolded alpha-synuclein via the connectome that might cause varying degrees of tissue damage based on local proper… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 101 publications
11
40
0
Order By: Relevance
“…This tissue expansion may represent an increase in CSF volume in the perisylvian area. These results confirm previous analyses of this dataset using slightly different methodology (Tremblay et al, 2021).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…This tissue expansion may represent an increase in CSF volume in the perisylvian area. These results confirm previous analyses of this dataset using slightly different methodology (Tremblay et al, 2021).…”
Section: Resultssupporting
confidence: 92%
“…This may be due to the lower number of scans acquired at the four-year time point (85 versus 105 at two years) causing reduced statistical power. Also, attrition bias may be present whereby the group of PD patients still in the study at year 4 had milder disease (Tremblay et al, 2021). Another possibility is that neuron and synapse loss over time modified the patients’ connectivity structures, leading to inaccuracies in modeling spread of pathology using a healthy connectome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of connectivity is in line with several studies showing that cerebral connectivity forecasts the atrophy seen in neurodegenerative diseases, 6668 including Parkinson’s disease. 20, 21 The influence of SNCA and GBA gene expression also agrees with mutations in these genes being significant risk factors for Parkinson’s disease and dementia with Lewy bodies. 6971 We observed that, whereas randomizing GBA expression always interfered with the model’s ability to recreate atrophy, the randomization of SNCA expression only led to a disruption at the 40% connection density, suggesting that GBA expression exerts an effect on the spread (and hence atrophy) that is more consistent than SNCA .…”
Section: Discussionmentioning
confidence: 55%
“…4, 1217 In line with this, MRI studies performed in patients with Parkinson’s disease also show that atrophy patterns are shaped by connectivity. 1820…”
Section: Introductionmentioning
confidence: 99%